2019
DOI: 10.1007/s13197-019-03695-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of fennel seed extract and determination of fenchone in commercial formulations by GC–MS method

Abstract: In the present study, various phytoconstituents of methanolic extract of Foeniculum vulgare were identified using gas-chromatography mass spectrometry (GC-MS) method. GC-MS method was also applied for the analysis of biomarker fenchone in extract and eight different commercial formulations. The mass of prepared extract and formulations A-D and H (commercial herbal mixtures and commercial extract) used for the analysis of fenchone was 10 g. However, the mass of formulations E-G (soft gelatin capsules) was 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Fennel (Foeniculum vulgare Mill; family: Apicaceae) is a biennial or perennial medicinal herb [1]. The main components of fennel seeds are essential oils which are important flavoring agents [1][2][3]. Various therapeutic activities in essential oils of fennel, such as "antioxidant [4][5][6][7], anti-inflammatory [7], analgesic [7], hepatoprotective [8], diuretic [2], antimicrobial [9], antibacterial [2,10,11], antifungal [12], antidiabetic [13], neuroprotective [14] and anti-tumor activities [15]," have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Fennel (Foeniculum vulgare Mill; family: Apicaceae) is a biennial or perennial medicinal herb [1]. The main components of fennel seeds are essential oils which are important flavoring agents [1][2][3]. Various therapeutic activities in essential oils of fennel, such as "antioxidant [4][5][6][7], anti-inflammatory [7], analgesic [7], hepatoprotective [8], diuretic [2], antimicrobial [9], antibacterial [2,10,11], antifungal [12], antidiabetic [13], neuroprotective [14] and anti-tumor activities [15]," have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…All these pharmacological activities are may be due to the medically active compounds, e.g. flavonoids, fatty acids, phenolics, and high complex protein known as phytochemicals [6,7]. The essential oil of fennel has composed ~ 87 volatile compounds [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The main volatile compounds have reported earlier from F. vulgare are anethol, methyl chavicol, fenchone and limonene as well as piperitenone and piperitenone oxide [9]. Among them, a GC/MS study revealed that anethole is the most abundant compound present in fennel essential oil [6]. The anethole is a monoterpene, a naturally existing aromatic compound isolated in fennel, tarragon, and basil [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical analysis of Foeniculum vulgare showed the presence of flavonoids, tannins, terpenes, alkaloids, and saponins. 20 The fennel characteristic flavours can be attributed to trans-anisole, estragole, and 1-octen-3-ol, 19 while the two major components of the essential oil are trans-anethol and fenchone. Melissa officinalis L. (lemon balm) leaves are rich in hydroxycinnamic acid derivatives and flavonoids.…”
Section: Introductionmentioning
confidence: 99%